Pradigma Baru Pelajaran SKI: Analisis Perkembangan Kurikulum 2013 Menuju Kurikulum Merdeka di Madrasah Ibtidaiyah - Badrun Fawaidi (SIRAJUDDIN : Jurnal Penelitian dan Kajian Pendidikan Islam, 2025)
This article aims to analyze the development of the 2013 Curriculum (K13) towards the Merdeka Curriculum in the subject of Islamic Cultural History (SKI) in Madrasah Ibtidaiyah. This curriculum transition phenomenon reflects a change in the national education paradigm from a competency-based approach to more contextual, reflective, and student-centered learning. This study uses a qualitative approach with a library research method, which aims to examine various academic sources, educational policies, and empirical research results related to the implementation of the Merdeka Curriculum in Islamic elementary schools. Data were collected through analysis of documents, scientific articles, and official government publications using purposive sampling techniques for relevant literature. Data analysis was conducted using thematic analysis to identify patterns, themes, and shifts in curriculum concepts in the context of SKI learning. The results of the study indicate that the transition from K13 to the Merdeka Curriculum is not only administrative but also paradigmatic. Three main themes were identified: (1) the reconstruction of the SKI learning philosophy, which places greater emphasis on the contextual interpretation of Islamic historical values; (2) the transformation of the role of teachers from conveyors of material to facilitators of reflective learning; and (3) the strengthening of the integration of Islamic values and the Pancasila student profile in learning activities. This study contributes to enriching the theoretical understanding of value-based curriculum adaptation in Islamic education and provides practical recommendations for madrasah teachers to develop more contextual and meaningful SKI learning. The implications of this study's findings emphasize the importance of curriculum innovation rooted in Islamic values while remaining adaptive to the challenges of 21st-century education.